2014
DOI: 10.1371/journal.pone.0091071
|View full text |Cite
|
Sign up to set email alerts
|

The Small Subunit 1 of the Arabidopsis Isopropylmalate Isomerase Is Required for Normal Growth and Development and the Early Stages of Glucosinolate Formation

Abstract: In Arabidopsis thaliana the evolutionary and functional relationship between Leu biosynthesis and the Met chain elongation pathway, the first part of glucosinolate formation, is well documented. Nevertheless the exact functions of some pathway components are still unclear. Isopropylmalate isomerase (IPMI), an enzyme usually involved in Leu biosynthesis, is a heterodimer consisting of a large and a small subunit. While the large protein is encoded by a single gene (ISOPROPYLMALATE ISOMERASE LARGE SUBUNIT1), thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 59 publications
6
35
0
Order By: Relevance
“…5). Glucosinolates are sulfur-rich, amino acidderived secondary metabolites that act as important determinants of plant growth, development, and defense against pathogens (Tantikanjana et al, 2001;Sønderby et al, 2010;He et al, 2011;Imhof et al, 2014). Some of the differentially regulated enzymes involved in glucosinolate biosynthesis (e.g.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…5). Glucosinolates are sulfur-rich, amino acidderived secondary metabolites that act as important determinants of plant growth, development, and defense against pathogens (Tantikanjana et al, 2001;Sønderby et al, 2010;He et al, 2011;Imhof et al, 2014). Some of the differentially regulated enzymes involved in glucosinolate biosynthesis (e.g.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…However, the high amino acid sequence identity of ~95% between A. thaliana LSU1 and Nicotiana sylvestris LSU, a close relative of N. benthamiana , suggests that functionality is not impaired. Recently, it was also demonstrated that A. thaliana SSUs to a certain extend can complement E. coli knockout mutants lacking the respective SSU homolog in LeuC (Imhof et al, 2014 ). Therefore, the increased production of DHM is most likely a result of a better ratio between large subunit to small subunit and the formation of a higher number of catalytically active IMPI heterodimers as a result of coexpressing LSU1 under the control of the same CaMV35S promoter as the other constructs.…”
Section: Resultsmentioning
confidence: 99%
“…SSU2 and SSU3 are generally associated with methionine chain elongation and SSU1 with LeuC (He et al, 2010 ). Nevertheless, it was recently hypothesized that SSU1 was actively involved in the first two cycles of methionine chain elongation (Imhof et al, 2014 ). Transport of α-keto acids (formed initially by cytosolic BCAT4 and after each cycle by the chloroplastic IPMDH enzyme) across the chloroplast membranes was suggested to be performed by the bile acid transporter 5 (BAT5) (Gigolashvili et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“… deKraker and Gershenzon (2011) demonstrated that a combination of the loss of the regulatory domain and a few additional amino acid exchanges can convert IPMS to MAM. In addition, the small subunit of the heteromeric IPMI was specialized into each pathway ( He et al , 2009 ; Knill et al , 2009 ; Imhof et al , 2014 ). Furthermore, it is demonstrated that a single amino acid substitution has the ability to interchange the substrate specificity of three IPMDHs ( He et al , 2011 a ).…”
Section: Discussionmentioning
confidence: 99%
“…The isomerization step is catalysed by isopropylmalate isomerases (IPMIs), which exist as heterodimeric enzymes and each consists of a large subunit encoded by a single gene, named LeuC , and a small subunit encoded by one of three genes, named LeuD1 , LeuD2 , and LeuD3 . LeuC has dual functions in both pathways, while the functions of different LeuD genes are diversified, with LeuD1 and LeuD2 functional in methionine chain elongation, whereas LeuD3 is functional in leucine biosynthesis ( Knill et al , 2009 ; Sawada et al , 2009 ; He et al , 2010 ; Imhof et al , 2014 ). Similarly, in the oxidative decarboxylation step, isopropylmalate decarboxylase 1 ( IPMDH1 ) works in methionine chain elongation, while IPMDH2 and IPMDH3 are involved in leucine biosynthesis ( He et al , 2009 2011 a ; Sawada et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%